Adverse events following immunization with Sinopharm (Vero Cell), inactivated COVID-19 vaccine (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Various types of COVID 19 vaccine are being used globally to control the current pandemic. Post-licensure surveillance of vaccine is essential to ensure the safety. This study aimed to determine Adverse Events Following Immunization (AEFIs) of China Sinopharm (Vero cell), the inactivated COVID-19 vaccine.Method: This is a cross sectional observational study conducted at Patan hospital, Patan Academy of Health Sciences (PAHS) after the approval from IRC. Vaccine recipient between April 7 to April 13 and May 16 to May 25 were contacted through a phone call after 72 h of vaccination to record the AEFIs. Pattern and distribution of AEFIs were analyzed. Ethical approval was taken from PAHS IRC.Result: A total of 6142 individual got the first dose of the vaccine and out of them we were able to contact 4574 through phone calls. Of the 4574, only 941 were included for the follow up phone call after the second dose of the vaccine. A total of 1336 AEFIs were reported in 868(19%) first dose vaccine recipients while 147 AFEIs were reported in 105(11.2%) second dose vaccine recipients.  The frequently reported AEFIs were pain at injection site, lethargy, headache, muscle ache and fever. All the AEFIs were mild to moderate in severity. Most of the AEFIs started within 24 h and resolved within 72 h.Conclusion: The Sinopharm (Vero cell) vaccine was found to have mild to moderate AEFIs in our study cohort and no case of severe AEFI was identified.